SILAGE CHARACTERISTICS OF MAIZE-FORAGE LEGUME MIXTURES ENSILED AT DIFFERENT HARVEST PERIODS - Mosebi, Poloko; Madakadze, Casper; Ntakatsane, Moeketsi; Ratsel, Ratsele (Chilean Journal of Agricultural & Animal Sciences, 2025)
This study was conducted to evaluate the effects of different harvest periods on the ensiling characteristics of maize-forage legume mixtures. Sole maize (Zea mays L.), sole common vetch (Vicia sativa L.), sole lablab (Lablab purpureus), maize + common vetch, and maize + lablab intercrops were harvested on different days after planting (DAP). The experiment was conducted using a completely randomized design with a 5 (forage systems) x 3 (harvest periods) factorial treatment arrangement and three replicates. Forage samples were ensiled at early, medium, and late harvest maturity: 50, 75 and 100 DAP. After ensiling in a laboratory mini-silo, samples were collected to determine chemical composition, microbial populations, and fermentation quality. Early harvest demonstrated lower contents of dry matter (DM) and crude protein, with values of 16.99 and 15.84% DM, respectively, in sole forage silages. High water-soluble carbohydrate concentrations and low fibre values (p < 0.05) were recorded when ensiled forage mixtures were harvested at the medium maturity stage. In mixed silages, the medium harvest time resulted in significantly lower populations of enterobacteria, yeasts and moulds, and higher populations of lactic acid bacteria, with values of 3.61, 4.83 and 5.17 log10 cfug-1, respectively. Lower pH values, NH3-N content, and greater lactic acid production (p < 0.05) were observed when the ensiled mixture and sole forages were harvested at the medium maturity stage compared to early and late harvest periods. Mixed silages from the medium harvest produced lower butyric acid and higher acetic and propionic acid concentrations (0.19, 1.07 and 1.25% DM, respectively) in the medium harvest, followed by silages from the late and early harvests. A medium harvest for ensiling mixed forage has the potential to produce high-quality silage for ruminant feeding.